Sustainability Cues Can Delay Consumption - Huang, Feifei; Siddiqui, Rafay A; Liu, Qianqian (Esther) (Journal of Consumer Research, 2025)
Abstract With the rise of environmental concerns in recent decades, many companies have joined the initiative to advertise and promote sustainable consumption. The current research examines how providing sustainability cues to consumers might have unintended consequences of which practitioners and policymakers may not be fully aware. One pilot study and 10 main studies, including two real-choice studies, show that a sustainability cue may delay consumption. That is, in an intertemporal choice, a sustainability cue can increase preference for a larger-later option over a smaller-sooner option. This effect occurs because a sustainability cue shifts a consumer’s temporal focus toward the future, leading to a shorter perceived wait time for the larger-later option. The findings further show that the delay does not emerge among those with strong green consumption values and can be circumvented if firms communicate the immediate need or instant payoff of sustainable actions. By investigating how sustainability cues shift consumer preferences between two options separated in time, the current research contributes to the literature on both sustainable consumption and intertemporal choice. The findings offer practitioners and policymakers guidelines to nudge consumers’ sustainable consumption more effectively.